(A Full-Day School sebagai salah satu alternatif untuk Meningkatkan Moral Kualitas Pendidikan) - M.Pd, Khulaifiyah, S.Pd (Perspektif, 2016)
A full-day school system actually not new anymore, because some private schools impliedthis system. The difference FDS proposed today is lied on its aplication which not only forstate school but also for private school in all area.Full-day school is a one of adabtability asfits solution to face the decrease of parents attention and development because of workingand also moral quality. But, the idea of full-day school might fit in the traditional schoolingpractices in Indonesia which can add the burden for teachers and students cost and energy.